2021
DOI: 10.3390/molecules26082138
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Isomeric and Enantiomeric Fractions of Pinene in Essential Oil of Picea abies Annual Needles during Growing Season

Abstract: Norway spruce (Picea abies (L.) H. Karst.) is one of the most important commercial tree species distributed naturally in the Boreal and subalpine forest zone of Europe. All parts of spruce trees, including needles, accumulate essential oils with a variety of chemical properties and ecological functions, such as modulating plant–insect communication. Annual needle samples from 15 trees (five from each of three habitats) of 15–17 years old were assayed for essential oils and their major compounds, including α-pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Large differences in enantiomeric composition of the chiral monoterpene hydrocarbons were found between the tissues [30] . Enantiomeric composition of monoterpenes in annual needles of Picea obovata was found to depend also on various factors during growing season [31] . Fungal inoculation significantly changed the enantiomeric composition of monoterpenes [32] .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Large differences in enantiomeric composition of the chiral monoterpene hydrocarbons were found between the tissues [30] . Enantiomeric composition of monoterpenes in annual needles of Picea obovata was found to depend also on various factors during growing season [31] . Fungal inoculation significantly changed the enantiomeric composition of monoterpenes [32] .…”
Section: Resultsmentioning
confidence: 95%
“…[30] Enantiomeric composition of monoterpenes in annual needles of Picea obovata was found to depend also on various factors during growing season. [31] Fungal inoculation significantly changed the enantiomeric composition of monoterpenes. [32] Enantiomeric composition of αpinene varies considerably between trees of different genetic origin.…”
Section: Enantiomeric Compositionmentioning
confidence: 99%
“…An important example of such a material is the branches of Picea abies (L.) H. Karst (Pinaceae), commonly known as European or Norway spruce, which is a tall essential-oil-bearing evergreen conifer used mostly for its wood [ 1 , 2 ]. P. abies accumulates volatile compounds in all parts of the plant, with the highest abundance in needles [ 3 ], which is also the least used part in the wood industry and the part of the plant with the largest volume [ 4 ]. Thus, in terms of sustainability, it is logical to exploit these needles for beneficial purposes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Japanese cedar (Cryptomeria japonica) (Bang et al, 2020), the maximum content of terpenes was observed in summer. Among most other conifers, such as white spruce (Pinus glauca) (von Rudloff, 1972), blue spruce (Pinus pungens) (von Rudloff, 1975), and Picea abies (Schnwitz et al, 1990;Kamaityt-Bukelskien et al, 2021), there is a similar seasonal pattern of variation in the number of terpenes. Similarly, flavonoids, such as anthocyanins, vary greatly across different seasons (Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%